2019
DOI: 10.1093/mnras/stz2242
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the M-dwarf Luminosity–Temperature–Radius relationships using Gaia DR2

Abstract: There is growing evidence that M-dwarf stars suffer radius inflation when compared to theoretical models, suggesting that models are missing some key physics required to completely describe stars at effective temperatures (T SED ) less than about 4000K. The advent of Gaia DR2 distances finally makes available large datasets to determine the nature and extent of this effect. We employ an all-sky sample, comprising of >15 000 stars, to determine empirical relationships between luminosity, temperature and radius.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 96 publications
3
34
0
Order By: Relevance
“…On the other side, the inability of the isochrone to adequately fit the bottom end of the sequence is a known problem (see e.g. Bell et al 2012;Morrell & Naylor 2019), and its discussion is beyond the scope of the present study.…”
Section: Colour-magnitude Diagrammentioning
confidence: 93%
“…On the other side, the inability of the isochrone to adequately fit the bottom end of the sequence is a known problem (see e.g. Bell et al 2012;Morrell & Naylor 2019), and its discussion is beyond the scope of the present study.…”
Section: Colour-magnitude Diagrammentioning
confidence: 93%
“…We estimated the radii of the M dwarfs using a semi-empirical mass-radius relationship for M dwarfs, based on a combination of a large dataset of M dwarf radius measurements (Morrell & Naylor 2019) and the mass-luminosity relation from Mann et al (2019). This semi-empirical mass-radius relationship will be presented in more detail in a future publication (Brown et al, in prep) and leads to more accurate radius predictions compared to theoretical massradius relationships, which tend to under-predict the radii of lowmass stars by 5-10 per cent (López-Morales & Ribas 2005;Parsons et al 2018).…”
Section: Dwarf Masses and Radiimentioning
confidence: 99%
“…The disadvantage of using the -band being the intrinsic faintness of low-mass stars at these wavelengths. Fortunately the sample of M dwarfs presented by Morrell & Naylor (2019) We used this relation to estimate the M dwarf contribution to the -band fluxes in all the non-magnetic systems. The excess -band flux was then determined to be from the white dwarf.…”
Section: White Dwarf Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…One area where significant effort has been made is EBs containing low-mass stars. There remains a "radius inflation" problem for stars below 1 M in EBs, where theoretical models underpredict the measured radii by up to 15% and overpredict their T eff s. It has been suggested that this is due to tidal effects causing a faster rotation and thus a stronger magnetic field [172][173][174], but this conflicts with the fact that it has also been seen in single stars [175][176][177], so there is no current consensus on the cause [178]. One way to investigate this is to study EBs containing low-mass stars, preferably with a range of mass, metallicity and rotational velocity.…”
Section: "Normal" Ebsmentioning
confidence: 99%